90Sr and 137Cs content in a wood along the southern fuel trace of Chernobyl radioactive fallout - L. M. Otreshko; M. A. Zhurba; A. M. Bilous; L. V. Yoschenko (Ядерна фізика та енергетика)
90Sr and 137Cs content in soil and unplanted wood of small size has been measured along the southern fuel trace of Chernobyl fallout, in Ivankov region of Kiev Oblast during 2012 - 2013. At present, due to biogenic and vertical 90Sr migration in soil of forests, content of 90Sr was reduced by 67 ± 18 % on average in 20-cm rooting-layer, containing less than 0.25 mg-eq of exchangeable calcium per 100 g of soil. Therefore, contamination of fuel wood with 90Sr today is depended weakly on exchangeable calcium content in soil (up to 1 mg-eq/100 g), considering the equal levels of the initial soil contamination with 90Sr. Values of 90Sr transfer factor (TF) to unplanted wood of deciduous trees and pine mounted to 34 ± 20 and 61 ± 56 (Bq/kg)/(kBq/m2), on average, that is in dozens exceeded the values, recommended by IAEA. In practice, there exist a risk to overrun hygienic norm value of 90Sr content in fuel wood and brushwood for the total area of Ivankov region.